Agreement of Program Directors With Clinical Competency Committees for Fellow Entrustment. (August 2020) - Mink, Richard; Herman, Bruce E; Carraccio, Carol; Aye, Tandy; Baffa, Jeanne M; Chess, Patricia R; Fussell, Jill J; Sauer, Cary G; Stafford, Diane E J; Weiss, Pnina; Curran, Megan L; Dammann, Christiane E L; et al.
Objectives: Fellowship program directors (FPD) and Clinical Competency Committees (CCCs) both assess fellow performance. We examined the association of entrustment levels determined by the FPD with those of the CCC for 6 common pediatric subspecialty entrustable professional activities (EPAs), hypothesizing there would be strong correlation and minimal bias between these raters. Methods: The FPDs and CCCs separately assigned a level of supervision to each of their fellows for 6 common pediatric subspecialty EPAs. For each EPA, we determined the correlation between FPD and CCC assessments and calculated bias as CCC minus FPD values for when the FPD was or was not a member of the CCC. In addition, we examined the effect of program size, FPD understanding of EPAs, and subspecialty on the correlations. Data were obtained in fall 2014 and spring 2015. Results: A total of 1040 fellows were assessed in the fall and 1048 in the spring. In both periods and for each EPA, there was a strong correlation between FPD and CCC supervision levels ( P < .001). The correlation was somewhat lower when the FPD was not a CCC member ( P < .001). Overall bias in both periods was small. Conclusions: The correlation between FPD and CCC assignment of EPA supervision levels is strong. Although slightly weaker when the FPD is not a CCC member, bias is small, so this is likely unimportant in determining fellow entrustment level. The similar performance ratings of FPDs and CCCs support the validity argument for EPAs as competency-based assessment tools.